Pengaruh Financial Literacy dan Risk Tolerance Terhadap Keputusan Investasi Pada Generasi Z di Kabupaten Bandung Barat - Nursinta, Noviyanti; Handayani, Rini (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to examine the influence of financial literacy and risk tolerance on investment decisions among Generation Z in West Bandung Regency. The research employs a quantitative approach using multiple linear regression analysis. The findings indicate that the financial literacy level of Generation Z falls into the "good" category, with strengths in managing savings and loans, although their understanding of different types of insurance remains relatively low. Similarly, risk tolerance is also categorized as good, particularly in terms of adjusting investments to financial conditions, although readiness to face potential losses remains a challenge. Investment decisions are likewise classified as good, with portfolio evaluation and adjustment strategies being the strongest aspect, while investment diversification is still less than optimal. Regression analysis results show that both financial literacy and risk tolerance, whether partially or simultaneously, have a positive and significant effect on investment decisions. The coefficient of determination (R²) of 0.551 indicates that 55.1% of the variation in investment decisions can be explained by these two variables. These findings emphasize that financial literacy and risk tolerance are crucial factors in shaping prudent investment behavior among young generations.